Development, carbon accumulation, and radiative forcing of a subarctic fen over the Holocene. (September 2014) - Mathijssen, Paul; Tuovinen, Juha-Pekka; Lohila, Annalea; Aurela, Mika; Juutinen, Sari; Laurila, Tuomas; Niemelä, Eerika; Tuittila, Eeva-Stiina; Väliranta, Minna
Three-dimensional reconstructions of peatland development patterns, carbon (C) dynamics and the related radiative forcing (RF) were analyzed to improve understanding of peatland–climate feedback mechanisms. We investigated vertical and horizontal peat growth patterns of a subarctic fen (Lompolojänkkä) located in Finnish Lapland. We calculated C accumulation rates and, based on these and modern gas exchange measurements, developed different scenarios of Holocene carbon dioxide (CO2 ) and methane (CH4 ) fluxes and reconstructed the RF driven by these fluxes. Holocene C accumulation rates at Lompolojänkkä ranged between 2 and 30 g C/m 2 /yr. Plant macrofossil analysis suggests that a fen environment prevailed throughout the Holocene. However, net C accumulation rates showed an extended period of low C accumulation during the mid-Holocene. At the same time, the lateral expansion rate of the peat area also decreased. The C flux scenarios resulted in a positive RF effect (warming) on the atmosphere following peat initiation. The RF turned negative (cooling) several hundreds to 2000 years after peat initiation. Subsequently, the cooling effect increased steadily and was only temporarily interrupted when CH4 emissions were forced to increase in the model. Although climate had an important effect on peatland C dynamics, its influence on RF was buffered by the long-term history of C uptake.